Characterising the hierarchical structure of urban-rural system at county level using a method based on interconnection analysis. (July 2022) - Cui, Jiaxing; Luo, Jing; Kong, Xuesong; Sun, Jianwei; Gu, Jiang
Abstract: Integrated urban–rural development is important in rural vitalisation. Most publications have focused on the structural system of urban agglomerations but ignored urban–rural systems at the county level. To fill this research gap, a three-level construction method using network analysis is proposed for investigating the structure of the interconnection of rural and urban systems at the county level. Hierarchical systems among towns, between towns and villages as well as among rural settlements are recognised by the interconnection strength measured by multiple methods. The development strategy of each town is decided using cross discrimination based on its nodality and network centrality. The hierarchy between towns and villages is characterised by interconnection analysis between towns and villages and one village would be designated as the hinterland of the destination town with the highest frequency of commuting behaviour. The hierarchy among rural settlements is characterised by their interdependence using gravity model and the central settlements are identified according to the forms of settlement clusters with their respective three spatial patterns (i.e., single-centre, dual-core and linear). The city- and sub-centres of Daye, economic hinterland of each town and central settlements were identified to provide guidelines for the development of rural planning and vitalisation. Our case study demonstrates the potential of the proposed analysis framework for the guidance of the urban-rural system construction. However, further investigation and alternative data sources are needed to fully reflect the interactive intensity between towns and rural settlements. Highlights: Recognizing the importance of the integrated urban–rural development in rural revitalization. Conceptual tools embracing network paradigm were successfully used to cognize the urban-rural system. The development strategy of each town was explored using cross discrimination based on its nodality and network centrality. The central settlements were identified according to the forms of settlement clusters.